To solve this, simply switch the X and y variables within one equation, and upon doing so, see and check if it equals to the other equation.
f(X) = -X + 4/5
Y = -X + 4/5
X = (-Y+4)/5
5X = -Y + 4
-Y = 5X - 4
Y = -5x + 4
Yes, by looking at the second equation it is an inverse of the first one.
Answer:
answer is a . x²-8x+16=32
x²-8x=32-16
Answer:
I think these should help.
Step-by-step explanation:
Answer:
3 + 9i
Step-by-step explanation:
(4 + 2i) - (1 - 7i)
distribute the (-)
(4 + 2i) - 1 + 7i
combine like terms
3 + 9i